Lectures on Spectroscopy - Nassima, Meftah (university of eloued جامعة الوادي, 2024)
These lessons, entitled Lectures on Spectroscopy, are a set of lessons directed to second year students of the L M D system physics specialty. The content of these lessons was prepared in accordance with the official program and was presented in a simple m anner. It is divided into six chapters. The first chapter is entitled Wave Particle Duality, to familiarize the student with the concept of blackbody radiation, the photoelectric effect, the Compton effect, and de Broglie waves. The second chapter gives in formation related to the planetary model of the atom, followed by the third chapter, which deals with atomic spectroscopy, which covers ionization potential, the excited state of the atom, atomic spectra, the Ritz principle, and the Heisenberg uncertainty principle. The fourth chapter is entitled: Atoms with multiple electrons. The fifth chapter explains the absorption and stimulated emission (laser effect). Finally, the sixth chapter is an introduction to molecular physics, which deals with diamolecules. T hese chapters are supported by illustrative diagrams and practical examples. ملخص هذه الدروس بعنوان محاضرات في التحليل الطيفي هي مجموعة دروس موجهة لطلاب السنة الثانية تخصص فيزياء نظام .L-M-D تم إعداد محتوى هذه الدروس وفق البرنامج الرسمي و تم عرضها بشكل مبسط. وهي مقسمة إلى ستة فصول. الفصل الأول بعنوان ازدواجية الموجة والجسيم، وذلك لتعريف الطالب بمفهوم إشعاع الجسم الأسود، والتأثير الكهروضوئي، وتأثير كومبتون، وموجات دي برولي. ويتناول الفصل الثاني معلومات تتعلق بالنموذج الكوكبي للذرة، ويتبعه الفصل الثالث الذي يتناول التحليل الطيفي الذري، والذي يغطي احتمال التأين، والحالة المثارة للذرة، والأطياف الذرية، ومبدأ ريتز، ومبدأ عدم اليقين هايزنبرغ. الفصل الرابع بعنوان الذرات ذات الإلكترونات المتعددة. الفصل الخامس يشرح الامتصاص والانبعاث المحفز )تأثير الليزر(. وأخيرًا، الفصل السادس عبارة عن مقدمة للفيزياء الجزيئية، والتي تتناول الجزيئات الثنائية. وجميع هذه الفصول مدعمة برسوم بيانية توضيحية وأمثلة عملية .
Intended for 2nd year physics students